Intraocular lens tilt and decentration measured by Scheimpflug camera following manual or femtosecond laser-created continuous circular capsulotomy - Kránitz, Kinga; Knorz, Michael C. (Journal of refractive surgery, 2012)
Purpose: To compare intraocular lens (IOL) decentration and tilt following a circular capsulotomy created with a femtosecond laser (laser CCC) to a manually performed continuous curvilinear capsulorrhexis (manual CCC). Methods: In a prospective, randomized study, a laser CCC (Alcon LenSx Inc) was performed in 20 eyes from 20 patients and a manual CCC was performed in 25 eyes from 25 patients.
Gesehen am 13.11.2018